Outsourcing and optimal nonlinear taxation: a note - Thomas Aronsson; Erkki Koskela (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper addresses outsourcing in the two-type optimal income tax model. If the government is able to control outsourcing via a direct tax instrument, outsourcing will not affect the marginal income tax structure. In the absence of a direct tax instrument, and under the plausible assumption that higher outsourcing increases the wage differential, the government will implement a lower marginal income tax rate for the low-ability type and a higher marginal income tax rate for the high-ability type than it would otherwise have done.
Keywords: H21; H25; J31; J62; 330; outsourcing; optimal nonlinear taxation; Outsourcing; Optimale Besteuerung; Körperschaftsteuer; Lohnstruktur; Arbeitsmobilität; Theorie